Answer:
C) Domain: all real numbers x except x = ±2
E) f(x) → ∞ as x → -2⁻ and as x → 2⁺, f(x) → -∞ as x → -2⁺ and as x → 2⁻
Explanation:
Given function:
![f(x)=(3x^2)/(x^2-4)](https://img.qammunity.org/2023/formulas/mathematics/college/fl39zxqe2og7qiipopwp42iq77o64l08d9.png)
The domain of a function is the set of all possible input values (x-values).
A rational function is undefined when the denominator is equal to zero.
The denominator of the given function is zero when:
![\implies x^2-4=0](https://img.qammunity.org/2023/formulas/mathematics/college/sfdkm0cunigk0d5bml1xjd24383c66mts3.png)
![\implies x^2=4](https://img.qammunity.org/2023/formulas/mathematics/college/n186yvdv3rvpozomhxlcpe06i6zl5534yo.png)
![\implies √(x^2)=√(4)](https://img.qammunity.org/2023/formulas/mathematics/college/1u2rzxc28xqcmlvtqmjpyb9xto67aod553.png)
![\implies x= \pm 2](https://img.qammunity.org/2023/formulas/mathematics/college/mb13lu2pvbpimcc5mkznj7k26cq63wsih7.png)
Therefore the domain of the function is:
- all real numbers x except x = ±2
The excluded x-values are x = -2 and x = 2.
To find the behaviour of the function near the excluded x-values, input values of x that are very near either side of excluded values:
![x \rightarrow -2^-: \quad f(-2.001)=(3(-2.001)^2)/((-2.001)^2-4)=3002.250...](https://img.qammunity.org/2023/formulas/mathematics/college/2ep914zasl4f0sw0aua16rydc37osr4vyq.png)
![x \rightarrow -2^+: \quad f(-1.999)=(3(-1.999)^2)/((-1.999)^2-4)=-2997,750...](https://img.qammunity.org/2023/formulas/mathematics/college/yumo9sc9p2ohyx1bu49cjao8x00gspljbv.png)
![x \rightarrow 2^-: \quad f(1.999)=(3(1.999)^2)/((1.999)^2-4)=-2997.750...](https://img.qammunity.org/2023/formulas/mathematics/college/dg2uj1w87yakd63ohu9gzjggs4ks2135iv.png)
![x \rightarrow -2^+: \quad f(2.001)=(3(2.001)^2)/((2.001)^2-4)=3002.250...](https://img.qammunity.org/2023/formulas/mathematics/college/2q7s52p21zr7dmdmml481697a3i46zaw01.png)
Therefore, the behaviour of the function near the excluded x-values:
- f(x) → +∞ as x → -2⁻
- f(x) → -∞ as x → -2⁺
- f(x) → -∞ as x → 2⁻
- f(x) → +∞ as x → 2⁺